Unprecedented Cyclization Catalyzed by a Cytochrome P450 in Benzastatin Biosynthesis - Tsutsumi, Hayama; Katsuyama, Yohei; Izumikawa, Miho; Takagi, Motoki; Fujie, Manabu; Satoh, Noriyuki; Shin-ya, Kazuo; Ohnishi, Yasuo (Journal of the American Chemical Society, 2018)
Benzastatins have unique structures probably derived from geranylated p-aminobenzoic acids. The indoline and tetrahydroquinoline scaffolds are presumably formed by cyclization of the geranyl moiety, but the cyclization mechanism was unknown. We studied the benzastatin biosynthetic gene cluster of Streptomyces sp. RI18; functions of the six enzymes encoded by it were analyzed by gene disruption in a heterologous host and in vitro enzyme assays. We propose the biosynthetic pathway for benzastatins in which a cytochrome P450 (BezE) is responsible for the cyclization of geranylated p-acetoxyaminobenzoic acids; BezE catalyzes elimination of acetic acid to form an iron nitrenoid, nitrene transfer to form an aziridine ring, and nucleophilic addition of hydroxide ion to C-10 and chloride ion to C-9 to generate the indoline and tetrahydroquinoline scaffolds, respectively. Discovery of this enzyme, which should be termed cytochrome P450 nitrene transferase, provides an important insight into the functional diversity of cytochrome P450.